Spontaneous Rupture of an Ovarian Artery Aneurysm: A Rare Postpartum Complication. (29th February 2016) - Enakpene, Christopher A.; Stern, Toni; Barzallo Salazar, Marco J.; Mukherjee, Pradip
Abstract : Background . Spontaneous rupture of an ovarian artery aneurysm is a rare but usually life-threatening event. It is most often associated with pregnancy or fibroids. Our case followed a normal vaginal delivery and then a delayed presentation with features similar to other less life-threatening postpartum conditions. The diagnosis could have been missed but for the meticulous and timely interventions which avoided catastrophic outcome. Case . This is a case of a multiparous woman with rupture of a left ovarian artery aneurysm, causing massive retroperitoneal hemorrhage and hematoma that required a combination of arterial embolization, percutaneous CT scan guided drainage, and surgical evacuation of the hematoma. Conclusion . Spontaneous rupture of ovarian artery should be considered as one of the differential diagnoses in the immediate postpartum period especially when the clinical symptoms do not correlate with the amount of blood loss. A high index of suspicion, prompt diagnosis, intervention, and a multidisciplinary approach in the management were the elements of a successful outcome in this case.